HUBUNGAN PENGGUNAAN METODE PEMBELAJARAN SOSIOFOTOGRAFI DENGAN MINAT BELAJAR SISWA DI SMA NEGERI 16 BEKASI - Hasan, Fanita; Kuntari, Septi; Widiansyah, Subhan (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to analyze whether there is a corelation between the use of Sociophotography learning methods and students' interest in learning. The research method used is quantitative. Respondents in this study were students of class X Social Sciences SMA Negeri 16 Bekasi City for the academic year 2021/2022, totaling 26 students, using purposive sampling technique. The data collection used is a closed questionnaires, observation and documentation. Then the results of the data from the questionnaire were analyzed with Pearson correlation statistics using SPSS version 16. The results of this study indicate that 1) The use of sociophotography learning methods is in the medium category: 2) Students' interest in learning is in the medium category; 3) The use of Sociophotography learning methods with students' interest in learning has a significant relationship with the strong category. The magnitude of the relationship between the X variable (Use of Sociophotography Learning Methods) with the Y variable (Students' Interest in Learning) is 0.788 or 78.8%. The amount of the contribution of the X variable to the Y variable is 62.1% and the remaining 37.9% is explained by other variables not discussed in this study.